Gyroscope-based assessment of temporal gait parameters during treadmill walking and running - McGrath, D.; Greene, B. R.; O`Donovan, K. J.; Caulfield, B. (Sports Engineering, 2012)
Wireless sensing solutions that provide accurate long-term monitoring of walking and running gait characteristics in a real-world environment would be an excellent tool for sport scientist researchers and practitioners. The purpose of this study was to compare the performance of a body-worn wireless gyroscope-based gait analysis application to a marker-based motion capture system for the detection of heel-strike and toe-off and subsequent calculation of gait parameters during walking and running. The gait application consists of a set of wireless inertial sensors and an adaptive algorithm for the calculation of temporal gait parameters. Five healthy subjects were asked to walk and run on a treadmill at two different walking speeds (2 and 4 kph) and at a jogging (8 kph) and running (12 kph) speed. Data were simultaneously acquired from both systems. True error, percentage error and ICC scores indicate that the adaptive algorithm successfully calculated strides times across all speeds. However, results showed poor to moderate agreement for stance and swing times. We conclude that this gait analysis platform is valid for determining stride times in both walking and running. This is a useful application, particularly in the sporting arena, where long-term monitoring of running gait characteristics outside of the laboratory is of interest.